Silica nanoparticles induce NLRP3 inflammasome activation in human primary immune cells (2017)
In recent years, the potential use of silica nanoparticles (SiNPs) among different biomedical fields has grown. A deep understanding of the physicochemical properties of nanoparticles (NPs) and their regulation of specific biological responses is crucial for the successful application of NPs. Exposure to NP physicochemical properties (size, shape, porosity, etc.) could result in deleterious effects on cellular functions, including a pro-inflammatory response mediated via activation of the NLRP3 inflammasome. The aim of this study was to evaluate the potential in vitro immunomodulatory effect of 12-nm and 200-nm SiNPs on the expression of pro-inflammatory cytokines and NLRP3 inflammasome components in human primary neutrophils and PBMCs. This study demonstrates that regardless of the size of the nanoparticles, SiNPs induce the production of pro-inflammatory cytokines in a dose-dependent manner. Induced IL-1ß production after exposure to SiNPs suggests the involvement of NLRP3 inflammasome components participation in this process. In conclusion, SiNPs induce the production of pro-inflammatory cytokines in a dose-dependent manner. Furthermore, our data suggest that the production and release of IL-1ß possibly occurs through the formation of the NLRP3 inflammasome. © 2017, © The Author(s) 2017.